Management of Geographic Tongue with Zinc and Vitamin B Complex Supplementation: A Case Report - Sarkar, Arup; Kona , Fatima Mazid; Mostafi, Alaul Qutub; Azam, Md Saiful; Choudhury , Md Nahid Khurram (Update Dental College Journal, 2024)
Background: Geographic tongue is a benign inflammatory condition characterized by erythematous patches on the tongue surface. While often self-limiting, it can cause discomfort and concern for patients. Nutritional deficiencies have been implicated in its etiology, but effective treatments remain limited. Case Presentation: A 23-year-old male from Rajshahi, Bangladesh presented to Update Dental College with asymptomatic erythematous patches on his tongue, consistent with geographic tongue. The patient had no significant medical history or known nutritional deficiencies. Methods: Based on potential associations with zinc and B vitamin deficiencies, the patient was prescribed daily zinc sulfate and a vitamin B complex supplement. Follow-up was scheduled after one week. Results: At 15 days follow-up, clinical examination revealed near-complete resolution of the erythematous patches. The patient reported no adverse effects from the supplementation and expressed satisfaction with the outcome. Conclusion: This case demonstrates rapid improvement of geographic tongue with zinc and vitamin B complex supplementation. While further research is needed, this approach may offer a promising treatment option for some patients with geographic tongue, potentially by addressing underlying nutritional deficiencies. Update Dent. Coll. j: 2024; 14(2): 36-37